Efficacy and safety of treatment regimens for patients with metastatic, locally advanced, or recurrent breast cancer carrying BRCA1/BRCA2 pathogenic variants: A network meta-analysis - Zhu, Yingxuan; Li, Yang; Liu, Weida; Zhou, Ruozhu; Tse, Lap Ah; Wang, Yang; Li, Wei (Frontiers in Oncology, 2023)
Objective Patients with breast cancer carrying BRCA1 and BRCA2 genetic alterations show poor prognoses. However, the efficacy of pharmacotherapies for patients with advanced breast cancer carrying BRCA1/2 pathogenic variants remains unclear. This study aimed to conduct a network meta-analysis to assess the efficacy and safety of various pharmacotherapies for patients with metastatic, locally advanced, or recurrent breast cancer carrying BRCA1/BRCA2 pathogenic variants. Methods A literature search was conducted using Embase, PubMed, and Cochrane Library (CENTRAL), from inception to 11th May 2022. The references of included articles were screened to identify relevant literature. This network meta-analysis included patients with metastatic locally advanced or recurrent breast cancer who received pharmacotherapy and carried deleterious variants of BRCA1/2. The Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines were followed for conducting and reporting this systematic meta-analysis. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) method was employed to evaluate evidential certainty. Frequentist random-effect model was applied. Results of objective response rate (ORR), progression-free survival (PFS), overall survival (OS), and rates of any-grade adverse events were presented. Results Nine randomized controlled trials were obtained comprising six treatment regimens, including 1912 patients with pathogenic variants of BRCA1 and BRCA2. The orchestration of PARP inhibitors with platinum-based chemotherapy was found to be the most effective with a pooled odds ratio (OR) of 3.52 (95% CI 2.14, 5.78) for ORR; 1.53 (1.34,1.76), 3.05 (1.79, 5.19), and 5.80 (1.42, 23.77) for 3-, 12-, and 24-month PFS, respectively, and 1.04 (1.00, 1.07), 1.76 (1.25, 2.49) and 2.31 (1.41, 3.77) for 3-, 12-, and 36-month OS, respectively compared to those receiving non-platinum-based chemotherapy. However, it posed an elevated risk of some adverse events. Platinum-based chemotherapy alone or PARP inhibitors markedly improved ORR, PFS, and OS compared to non-platinum-based chemotherapy. Interestingly, platinum-based chemotherapy surpassed PARP inhibitors in terms of efficacy. Evidence on programmed death-ligand 1(PD-L1) inhibitors and sacituzumab govitecan (SG) suggested low quality and insignificant results. Conclusions Among all treatment regimens, PARP inhibitors with platinum exhibited the best efficacy, although with a trade-off of elevated risk of some types of adverse events. Future research on direct comparisons between different treatment regimens specifically targeting patients with breast cancer carrying BRCA1/2 pathogenic variants with a pre-specified adequate sample size is warranted.